Culture Method and PCR for the Detection of Helicobacter pylori in Drinking Water in Basrah Governorate Iraq - A. A. Al-Sulami; T. A. A. Al-Edani; A. A. Al-Abdula (Gastroenterology Research and Practice)
Helicobacter pylori is recognized by the World Health Organization to be the primary cause of peptic ulcers, chronic gastritis, and stomach cancer, though the source of human infection is not well understood. One of the problems in understanding the source of human contamination is the difficulty in isolating the organism from the environment. However, the combination of PCR results with those of culturing of 471 drinking water samples can provide a more accurate picture of H. pylori detection. In this method 78 presumptive H. pylori colonies out of 266 tap water samples were obtained in the preliminary detection on modified Columbia agar (MCUA) slant relying on urease positivity with a rate of 29.3%. However, only 11 out of them were confirmed by Gram staining and biochemical tests reducing the rate to 4.13% whereas only 3 (1.46%) from 205 reverse osmosis (RO) water samples. Furthermore, only 6 (54.5%) out of the 11 isolates from tap water and 1 (33.3%) of the 3 RO isolates were confirmed by 16SrRNA PCR. Thus PCR confirmation reduced the rate to 2.2%. In addition, only 4 (4%) of 100 tap water samples negative for H. pylori by culture method were H. pylori positive by 16SrRNA. Water samples were collected from 24 districts of Basrah Governorate from February–December 2009. The direct recovery of H. pylori from drinking water is both alarming and scientifically exciting in terms of the investigation of its epidemiology.